Pengaruh Model Pembelajaran Think Pair Share (TPS) dengan Berbantuan Quizizz terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Naibaho, Angelika; Manurung, Nurliani (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
This study was motivated by the low mathematical problem-solving ability of students at SMA Negeri 2 Percut Sei Tuan, where students experienced difficulties in solving word problems and tended to be passive during learning activities. Mathematical problem-solving ability is a crucial competence that supports logical thinking, creativity, and readiness to face real-life challenges; therefore, improving this ability is essential for students’ overall learning outcomes. The study aimed to examine the effect of the Think Pair Share (TPS) learning model assisted by Quizizz on students’ mathematical problem-solving ability. The research employed a quasi-experimental design involving two classes, each consisting of 34 students. Data were collected through questionnaires, pretests, and posttests. The experimental class was taught using the TPS learning model assisted by Quizizz, while the control class received conventional instruction. Prior analysis showed that both classes were normally distributed and had homogeneous variances. Posttest results indicated a significant difference between the experimental and control classes, with an independent two-sample t-test yielding a Sig. (2-tailed) value of 0.000 and t-count (4.783) greater than t-table (1.997). Furthermore, simple linear regression analysis produced the equation with a significance value of 0.000, indicating that the TPS model assisted by Quizizz contributed 12.7% to students’ mathematical problem-solving ability. The findings demonstrate that the TPS learning model integrated with a gamified platform effectively enhances student engagement and mathematical problem-solving performance by creating a more interactive and motivating learning environment.